A kind of insulating coating for automobile and preparation method thereof
By combining modified acrylic resin and modified silica, a tight crosslinking network is formed, which solves the problems of insufficient insulation, thermal conductivity and water resistance of new energy vehicle battery coatings, and improves the insulation resistance, wear resistance and water resistance of the coating. , provides safer battery pack protection.
Patent Information
- Application Number
- CN202411567425.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
New energy vehicle batteries are prone to burning and explosion when they are impacted or squeezed. The existing fire-resistant coatings lack insulation, water resistance and heat dissipation properties, and the raw materials are complex and have poor dispersion.
Modified acrylic resin and modified silica are used as the main raw materials to form a tight organic and inorganic cross-linking network through specific preparation methods to improve the insulation, thermal conductivity and water resistance of the coating, and modify the silica by curcumin. Improve dispersion and hydrophobic properties.
It significantly improves the insulation resistance, wear resistance and water resistance of the coating, enhances the mechanical properties and stability of the coating, and provides excellent insulation, thermal conductivity and waterproofing effects.
Smart Images

Figure CN119060603B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile insulating coatings, and in particular to an insulating coating for automobiles and a preparation method thereof. Background Art
[0002] New energy vehicles are vehicles that rely on clean and pollution-free new energy as a driving force, and batteries are one of the important components of new energy vehicles. At present, the biggest problem with new energy vehicle batteries is that the battery pack is easily damaged by collision or extrusion, causing the battery to burn and explode, and the safety problem is very serious. At present, fire retardant coatings, flame-retardant battery shells, etc. are mainly used to improve the fire resistance of battery components. Chinese patent CN116333566B discloses a zero-VOC two-component fire-retardant expansion coating for a new energy battery shell and a preparation method and a battery compartment. The two-component fire-retardant expansion coating prepared using phenolic epoxy resin, brominated epoxy resin, liquid flame retardant, ammonium polyphosphate, melamine, etc. as the main raw materials has excellent flame retardant and heat insulation, structural stability and safety. However, the raw materials of the fire retardant coating of the patent are complicated and do not have insulation, water resistance and other properties. Water-based acrylic resin has the advantages of environmental protection and good film-forming properties, and has important applications in coatings, new energy vehicles, etc. However, water-based acrylic resin does not have flame retardant properties, and has poor water resistance, insulation and thermal conductivity and heat dissipation properties; nano boron nitride has high thermal conductivity and resistivity, and is widely used in insulation materials, thermal conductivity and heat dissipation materials, etc., but its dispersibility and compatibility with polymer material matrices are poor. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides an insulating coating for automobiles and a preparation method thereof.
[0004] The present invention is achieved through the following technical solutions:
[0005] An insulating coating for automobiles, comprising the following raw materials in parts by weight: 80-100 parts of modified acrylic resin, 15-18 parts of modified silicon dioxide, 2-3 parts of dispersant, 0.5-0.7 parts of defoamer, 0.3-0.5 parts of leveling agent, and 80-100 parts of deionized water;
[0006] The preparation method of the modified acrylic resin comprises the following steps:
[0007] (1) Aluminum trichloride is added to deionized water, stirred at 500-600 rpm for 30 min, ethylenediamine is added dropwise at a rate of 0.2-0.3 mL / min, and the mixture is transferred to a polytetrafluoroethylene reactor, heat treated at 180-200°C for 16-18 h, cooled to room temperature, centrifuged at 5000 rpm for 30 min, the precipitate is washed with deionized water and anhydrous ethanol, and dried at 80°C to obtain aluminum hydroxide;
[0008] (2) adding the aluminum hydroxide obtained in step (1) to deionized water, and ultrasonicating at 500 W for 15 min to obtain a mixed solution A; adding triethoxy-2-propylenesilane to tetrahydrofuran, and ultrasonicating at 500 W for 5 min to obtain a mixed solution B; adding the mixed solution B to the mixed solution A, stirring at 600 rpm, stirring at 25° C. for 30 min, stirring at 120° C. for 90 min, standing at 4° C. for 2-3 h, centrifuging at 5000-6000 rpm for 30 min, washing the precipitate with deionized water, and drying at 60° C. to obtain modified aluminum oxide;
[0009] (3) Add the modified alumina obtained in step (2) to n-butanol, ultrasonicate at 300-400 W for 30 min, then raise the temperature to 90°C, introduce nitrogen, add styrene, acrylic acid, butyl acrylate, methyl methacrylate and dibenzoyl peroxide, react for 3-4 h, and heat at 120°C for 10 min. -3 MPa to remove n-butanol under reduced pressure to obtain modified acrylic resin;
[0010] The preparation method of the modified silicon dioxide comprises the following steps:
[0011] (a) Adding silica with a particle size of 50 nm into tetrahydrofuran, ultrasonicating at 300 W for 10-15 min to obtain a silica dispersion; dissolving 3-aminopropyltriethoxysilane (APTES) in tetrahydrofuran to obtain an APTES solution, adding the APTES solution into the silica dispersion, heating and reflux at 60°C for 6 h, cooling to room temperature, centrifuging at 5000 rpm for 15 min, and drying the precipitate at 90°C to obtain amino silica;
[0012] (b) adding malonic acid to deionized water to obtain a malonic acid solution, dissolving N,N'-carbonyldiimidazole (CDI) in tetrahydrofuran to obtain a CDI solution, and adding the CDI solution dropwise to the malonic acid solution under nitrogen protection at a dropping speed of 0.8-1.2 mL / min. After the dropwise addition is completed, stirring is performed at 100 rpm at room temperature for 4-5 h, and then the aminosilica obtained in step (a) is added, and stirring is continued for 4-5 h. Centrifugation is performed at 8000 rpm for 30 min, and the precipitate is washed with distilled water for 4-6 times, and dried at 100° C. to obtain carboxyl silica;
[0013] (c) adding the carboxysilica obtained in step (b) to tetrahydrofuran, and ultrasonicating at 500 W for 10 min to obtain a carboxysilica dispersion, adding 1-hydroxybenzotriazole and N-N'-dicyclohexylcarbodiimide to the carboxysilica dispersion, and stirring at 25° C. and 100-150 rpm for 3-4 h to obtain an activated carboxysilica dispersion;
[0014] (d) curcumin is dissolved in tetrahydrofuran to obtain a curcumin solution, the activated carboxyl silica dispersion in step (c) is mixed with the curcumin solution, reacted at 70-80° C. for 18-20 h under nitrogen protection, allowed to stand at 4° C. for 5-6 h, centrifuged at 5000 rpm for 30 min, the precipitate is washed with anhydrous ethanol and deionized water, and vacuum dried at 50° C. to constant weight to obtain modified silica.
[0015] Furthermore, the dispersant is preferably BYK-220S.
[0016] Furthermore, the defoaming agent is preferably THIX-318.
[0017] Furthermore, the leveling agent is preferably BYK-346.
[0018] Furthermore, in step (1), the ratio of aluminum chloride to deionized water is 1 g:20 mL.
[0019] Furthermore, in step (1), the ratio of aluminum chloride to ethylenediamine is 15 g:8 mL.
[0020] Furthermore, in step (2), in the mixed solution A, the ratio of aluminum oxide hydroxide to deionized water is 2 mg:1 mL.
[0021] Furthermore, in step (2), in the mixed solution B, the ratio of triethoxy-2-propylenesilane to tetrahydrofuran is 2-3 mg:1 mL.
[0022] Furthermore, in step (2), the volume ratio of the mixed solution A to the mixed solution B is 1:1.
[0023] Furthermore, in step (3), the ratio of the modified alumina to n-butanol is 1 g:100 mL.
[0024] Furthermore, in step (3), the mass ratio of the modified alumina, styrene, methyl methacrylate, acrylic acid, butyl acrylate and dibenzoyl peroxide is 2:16-18:32:6-7:45:0.8-1.2.
[0025] Furthermore, in step (a), the ratio of silicon dioxide to tetrahydrofuran in the silicon dioxide dispersion is 1 g: 12-15 mL.
[0026] Furthermore, in step (a), the ratio of APTES to tetrahydrofuran in the APTES solution is 1 g:1.5-2 mL.
[0027] Furthermore, in step (a), the mass ratio of APTES to silicon dioxide is 2-3:1.
[0028] Furthermore, in step (b), the ratio of malonic acid to deionized water in the malonic acid solution is 1 g:4-6 mL.
[0029] Furthermore, in step (b), the ratio of CDI to tetrahydrofuran in the CDI solution is 1 g:5-7 mL.
[0030] Furthermore, in step (b), the mass ratio of malonic acid to CDI is 1:0.6-0.8.
[0031] Furthermore, in step (b), the mass ratio of aminosilica to malonic acid is 1:2-3.
[0032] Furthermore, in step (c), the ratio of carboxysilica to tetrahydrofuran in the carboxysilica dispersion is 1 g:15 mL.
[0033] Furthermore, in step (c), the mass ratio of the carboxysilicon dioxide, 1-hydroxybenzotriazole and N,N'-dicyclohexylcarbodiimide is 5:1:2.
[0034] Furthermore, in step (d), the ratio of curcumin to tetrahydrofuran in the curcumin solution is 1 g: 8-10 mL.
[0035] Furthermore, in step (d), the volume ratio of the curcumin solution to the activated carboxysilicon dioxide dispersion is 1:1.8-2.2.
[0036] Furthermore, the present invention also provides a method for preparing the automotive insulating coating, comprising the following steps: adding modified acrylic resin to deionized water, stirring at 500 rpm for 30 min, adding modified silica, dispersant, defoaming agent, and leveling agent, ultrasonically treating for 1 h at 25 kHz, and stirring at a stirring speed of 1000 r / min for 12-15 min to obtain the automotive insulating coating.
[0037] Furthermore, the present invention also provides the application of the automotive insulating coating in new energy vehicle batteries.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The invention provides an insulating coating for automobiles and a preparation method thereof. Modified acrylic resin is used as a substrate and modified silicon dioxide is used as a filler, so that the insulation of the coating can be improved. The modified alumina and modified silicon dioxide have good dispersibility, synergistically enhance the effect, and improve the stability. When the coating is subjected to external force, the load can be effectively transferred to the alumina and silicon dioxide with strong physical and mechanical properties, thereby improving the wear resistance and comprehensively improving the performance of the coating. The invention modifies aluminum oxide, introduces alkenyl groups on the surface of aluminum oxide, and copolymerizes with monomers such as styrene and acrylic acid, so that the modified aluminum oxide participates in the polymerization process of acrylic resin, thereby cross-linking and grafting the aluminum oxide into the acrylic resin, enhancing the interface bonding performance between the two, and improving the dispersibility of the aluminum oxide. The aluminum oxide itself has excellent insulation performance, high resistivity and thermal conductivity, and is evenly dispersed in the acrylic resin water-based paint, which significantly improves the insulation resistance coefficient of the paint coating and has excellent insulation and thermal conductivity and heat dissipation performance. In addition, the modified aluminum oxide and the acrylic resin molecular chain undergo chemical cross-linking to form a tight organic-inorganic cross-linking network, which is beneficial to reducing the water absorption rate of the coating, thereby improving the water resistance and improving the mechanical properties. The present invention dopes filler modified silicon dioxide into a resin material, introduces curcumin, improves the dispersibility of silicon dioxide, enables the silicon dioxide to be evenly dispersed in the resin material, relies on the excellent insulation performance of silicon dioxide, improves the insulation of the prepared coating, and can also improve the wear resistance of the coating; curcumin has a hydrophobic group, and the modified silicon dioxide is dispersed in the resin. The introduction of curcumin can improve the hydrophobicity of the coating, reduce the material's ability to absorb water, improve water resistance, and achieve a waterproof effect; the modified silicon dioxide can be cross-linked with the modified acrylic resin through hydrogen bonds, thereby improving the mechanical strength, and improving the water resistance and stability of the coating to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 The insulation test results of the insulating coatings described in Examples 1-3 and Comparative Examples 1-3 of the present invention are as follows;
[0042] Figure 2 The wear resistance test results of the insulating coatings described in Examples 1-3 and Comparative Examples 1-3 of the present invention are as follows;
[0043] Figure 3 These are the impact resistance test results of the insulating coatings described in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention are purchased through commercial channels.
[0045] Example 1: This example provides an insulating coating for automobiles, comprising the following raw materials in parts by weight: 100 parts of modified acrylic resin, 18 parts of modified silica, 3 parts of BYK-220S, 0.7 parts of THIX-318, 0.5 parts of BYK-346, and 100 parts of deionized water.
[0046] The preparation method of modified acrylic resin comprises the following steps:
[0047] (1) 1.5 g aluminum chloride was added to 30 mL deionized water, stirred at 600 rpm for 30 min, 0.8 mL ethylenediamine was added dropwise at a rate of 0.3 mL / min, and the mixture was transferred to a polytetrafluoroethylene reactor. The mixture was heat treated at 200 °C for 18 h, cooled to room temperature, and centrifuged at 5000 rpm for 30 min. The precipitate was washed with deionized water and anhydrous ethanol, and dried at 80 °C to obtain aluminum hydroxide.
[0048] (2) 2 g of the aluminum hydroxide obtained in step (1) was added to 1 L of deionized water and ultrasonicated at 500 W for 15 min to obtain a mixed solution A. 3 g of triethoxy-2-propylenesilane was added to 1 L of tetrahydrofuran and ultrasonicated at 500 W for 5 min to obtain a mixed solution B. 1 L of the mixed solution B was added to 1 L of the mixed solution A, and the mixture was stirred at 600 rpm, stirred at 25° C. for 30 min, stirred at 120° C. for 90 min, allowed to stand at 4° C. for 3 h, and centrifuged at 6000 rpm for 30 min. The precipitate was washed with deionized water and dried at 60° C. to obtain modified aluminum oxide.
[0049] (3) Add 2 g of the modified alumina obtained in step (2) to 200 mL of n-butanol, ultrasonicate at 400 W for 30 min, heat to 90 °C, introduce nitrogen, add 18 g of styrene, 7 g of acrylic acid, 45 g of butyl acrylate, 32 g of methyl methacrylate and 1.2 g of dibenzoyl peroxide, react for 4 h at 120 °C, 10 -3 MPa under reduced pressure to remove n-butanol to obtain modified acrylic resin.
[0050] The preparation method of modified silicon dioxide comprises the following steps:
[0051] (a) 1 g of silica with a particle size of 50 nm was added to 15 mL of tetrahydrofuran and ultrasonicated at 300 W for 15 min to obtain a silica dispersion; 3 g of 3-aminopropyltriethoxysilane (APTES) was dissolved in 6 mL of tetrahydrofuran to obtain an APTES solution, and the APTES solution was added to the silica dispersion, heated under reflux at 60 °C for 6 h, cooled to room temperature, centrifuged at 5000 rpm for 15 min, and the precipitate was dried at 90 °C to obtain amino silica;
[0052] (b) 3 g of malonic acid was added to 18 mL of deionized water to obtain a malonic acid solution, 2.4 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 16.8 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the malonic acid solution under nitrogen protection at a dropping rate of 1.2 mL / min. After the dropwise addition was completed, the mixture was stirred at 100 rpm for 5 h at room temperature, and then 1.5 g of aminosilica obtained in step (a) was added, and the mixture was stirred for 5 h. The mixture was centrifuged at 8000 rpm for 30 min, and the precipitate was washed 6 times with distilled water and dried at 100°C to obtain carboxyl silica;
[0053] (c) adding 1.5 g of the carboxysilica obtained in step (b) to 22.5 mL of tetrahydrofuran, and ultrasonicating at 500 W for 10 min to obtain a carboxysilica dispersion, adding 0.3 g of 1-hydroxybenzotriazole and 0.6 g of N-N'-dicyclohexylcarbodiimide to the carboxysilica dispersion, and stirring at 25°C and 150 rpm for 4 h to obtain an activated carboxysilica dispersion;
[0054] (d) 1 g of curcumin was dissolved in 10 mL of tetrahydrofuran to obtain a curcumin solution, 2.2 mL of the activated carboxyl silica dispersion prepared in step (c) was mixed with 1 mL of the curcumin solution, reacted at 80° C. for 20 h under nitrogen protection, allowed to stand at 4° C. for 6 h, centrifuged at 5000 rpm for 30 min, the precipitate was washed with anhydrous ethanol and deionized water, and dried under vacuum at 50° C. to constant weight to obtain modified silica.
[0055] This embodiment also provides a method for preparing the automotive insulating coating, comprising the following steps: adding modified acrylic resin to deionized water, stirring at 500 rpm for 30 min, adding modified silica, dispersant, defoamer, and leveling agent, ultrasonicating at 25 kHz for 1 h, and stirring at a stirring speed of 1000 r / min for 15 min to obtain the automotive insulating coating.
[0056] This embodiment also provides the application of the automotive insulating coating in new energy vehicle batteries.
[0057] Example 2: This example provides an insulating coating for automobiles, comprising the following raw materials in parts by weight: 80 parts of modified acrylic resin, 15 parts of modified silica, 2 parts of BYK-220S, 0.5 parts of THIX-318, 0.3 parts of leveling agent BYK-346, and 80 parts of deionized water.
[0058] The preparation method of modified acrylic resin comprises the following steps:
[0059] (1) 1.5 g aluminum trichloride was added to 30 mL deionized water, stirred at 500 rpm for 30 min, 0.8 mL ethylenediamine was added dropwise at a rate of 0.2 mL / min, and the mixture was transferred to a polytetrafluoroethylene reactor. The mixture was heat treated at 180 °C for 16 h, cooled to room temperature, and centrifuged at 5000 rpm for 30 min. The precipitate was washed with deionized water and anhydrous ethanol, and dried at 80 °C to obtain aluminum hydroxide.
[0060] (2) 2 g of the aluminum hydroxide obtained in step (1) was added to 1 L of deionized water and ultrasonicated at 500 W for 15 min to obtain a mixed solution A. 2 g of triethoxy-2-propylenesilane was added to 1 L of tetrahydrofuran and ultrasonicated at 500 W for 5 min to obtain a mixed solution B. 1 L of the mixed solution B was added to 1 L of the mixed solution A, and the mixture was stirred at 600 rpm, stirred at 25° C. for 30 min, stirred at 120° C. for 90 min, allowed to stand at 4° C. for 2 h, and centrifuged at 5000 rpm for 30 min. The precipitate was washed with deionized water and dried at 60° C. to obtain modified aluminum oxide.
[0061] (3) Add 2 g of the modified alumina obtained in step (2) to 200 mL of n-butanol, ultrasonicate at 300 W for 30 min, heat to 90 °C, introduce nitrogen, add 16 g of styrene, 6 g of acrylic acid, 45 g of butyl acrylate, 32 g of methyl methacrylate and 0.8 g of dibenzoyl peroxide, react for 3 h at 120 °C, 10 -3 MPa under reduced pressure to remove n-butanol to obtain modified acrylic resin.
[0062] The preparation method of modified silicon dioxide comprises the following steps:
[0063] (a) 1 g of silica with a particle size of 50 nm was added to 12 mL of tetrahydrofuran and ultrasonicated at 300 W for 10 min to obtain a silica dispersion; 2 g of 3-aminopropyltriethoxysilane (APTES) was dissolved in 3 mL of tetrahydrofuran to obtain an APTES solution, and the APTES solution was added to the silica dispersion, heated under reflux at 60 °C for 6 h, cooled to room temperature, centrifuged at 5000 rpm for 15 min, and the precipitate was dried at 90 °C to obtain amino silica;
[0064] (b) 3 g of malonic acid was added to 12 mL of deionized water to obtain a malonic acid solution, 1.8 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 9 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the malonic acid solution under nitrogen protection at a dropping rate of 0.8 mL / min. After the dropwise addition was completed, the mixture was stirred at 100 rpm for 4 h at room temperature, and then 1 g of aminosilica obtained in step (a) was added, and the mixture was stirred for 4 h. The mixture was centrifuged at 8000 rpm for 30 min, and the precipitate was washed 4 times with distilled water and dried at 100°C to obtain carboxyl silica;
[0065] (c) adding 1.5 g of the carboxysilica obtained in step (b) to 22.5 mL of tetrahydrofuran, and ultrasonicating at 500 W for 10 min to obtain a carboxysilica dispersion, adding 0.3 g of 1-hydroxybenzotriazole and 0.6 g of N-N'-dicyclohexylcarbodiimide to the carboxysilica dispersion, and stirring at 25°C and 100 rpm for 3 h to obtain an activated carboxysilica dispersion;
[0066] (d) 1 g of curcumin was dissolved in 8 mL of tetrahydrofuran to obtain a curcumin solution, 1.8 mL of the activated carboxyl silica dispersion prepared in step (c) was mixed with 1 mL of the curcumin solution, reacted at 70° C. for 18 h under nitrogen protection, allowed to stand at 4° C. for 5 h, centrifuged at 5000 rpm for 30 min, the precipitate was washed with anhydrous ethanol and deionized water, and dried at 50° C. in a vacuum oven to constant weight to obtain modified silica.
[0067] This embodiment also provides a method for preparing the automotive insulating coating, comprising the following steps: adding modified acrylic resin to deionized water, stirring at 500 rpm for 30 min, adding modified silica, dispersant, defoaming agent, and leveling agent, ultrasonicating at 25 kHz for 1 h, and stirring at a stirring speed of 1000 r / min for 12 min to obtain the automotive insulating coating.
[0068] This embodiment also provides the application of the automotive insulating coating in new energy vehicle batteries.
[0069] Example 3: This example provides an insulating coating for automobiles, comprising the following raw materials in parts by weight: 90 parts of modified acrylic resin, 16 parts of modified silica, 2.5 parts of BYK-220S, 0.6 parts of THIX-318, 0.4 parts of BYK-346, and 90 parts of deionized water.
[0070] The preparation method of modified acrylic resin comprises the following steps:
[0071] (1) 1.5 g aluminum chloride was added to 30 mL deionized water, stirred at 550 rpm for 30 min, 0.8 mL ethylenediamine was added dropwise at a rate of 0.25 mL / min, and the mixture was transferred to a polytetrafluoroethylene reactor. The mixture was heat treated at 190 °C for 17 h, cooled to room temperature, and centrifuged at 5000 rpm for 30 min. The precipitate was washed with deionized water and anhydrous ethanol, and dried at 80 °C to obtain aluminum hydroxide.
[0072] (2) 2 g of the aluminum hydroxide obtained in step (1) was added to 1 L of deionized water and ultrasonicated at 500 W for 15 min to obtain a mixed solution A. 2.5 g of triethoxy-2-propylenesilane was added to 1 L of tetrahydrofuran and ultrasonicated at 500 W for 5 min to obtain a mixed solution B. 1 L of the mixed solution B was added to 1 L of the mixed solution A, and the mixture was stirred at 600 rpm, stirred at 25° C. for 30 min, stirred at 120° C. for 90 min, allowed to stand at 4° C. for 2.5 h, and centrifuged at 5500 rpm for 30 min. The precipitate was washed with deionized water and dried at 60° C. to obtain modified aluminum oxide.
[0073] (3) 2 g of the modified alumina obtained in step (2) was added to 200 mL of n-butanol, and the mixture was ultrasonicated at 350 W for 30 min, then the temperature was raised to 90°C, nitrogen was introduced, 17 g of styrene, 6.5 g of acrylic acid, 45 g of butyl acrylate, 32 g of methyl methacrylate and 1 g of dibenzoyl peroxide were added, and the reaction was continued for 3.5 h at 120°C and 10 -3 MPa under reduced pressure to remove n-butanol to obtain modified acrylic resin.
[0074] The preparation method of modified silicon dioxide comprises the following steps:
[0075] (a) 1 g of silica with a particle size of 50 nm was added to 14 mL of tetrahydrofuran and ultrasonicated at 300 W for 12 min to obtain a silica dispersion; 2.5 g of 3-aminopropyltriethoxysilane (APTES) was dissolved in 4.5 mL of tetrahydrofuran to obtain an APTES solution, and the APTES solution was added to the silica dispersion, heated under reflux at 60 °C for 6 h, cooled to room temperature, centrifuged at 5000 rpm for 15 min, and the precipitate was dried at 90 °C to obtain amino silica;
[0076] (b) 3 g of malonic acid was added to 15 mL of deionized water to obtain a malonic acid solution, 2.1 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 12.6 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the malonic acid solution under nitrogen protection at a dropping rate of 1 mL / min. After the addition was completed, the mixture was stirred at 100 rpm at room temperature for 4.5 h, and then 1.2 g of aminosilica obtained in step (a) was added, and the mixture was stirred for 4.5 h. The mixture was centrifuged at 8000 rpm for 30 min, and the precipitate was washed 5 times with distilled water and dried at 100°C to obtain carboxyl silica;
[0077] (c) adding 1.5 g of the carboxysilica obtained in step (b) to 22.5 mL of tetrahydrofuran, and ultrasonicating at 500 W for 10 min to obtain a carboxysilica dispersion, adding 0.3 g of 1-hydroxybenzotriazole and 0.6 g of N-N'-dicyclohexylcarbodiimide to the carboxysilica dispersion, and stirring at 25° C. and 120 rpm for 3.5 h to obtain an activated carboxysilica dispersion;
[0078] (d) 1 g of curcumin was dissolved in 9 mL of tetrahydrofuran to obtain a curcumin solution, 2 mL of the activated carboxyl silica dispersion prepared in step (c) was mixed with 1 mL of the curcumin solution, reacted at 75° C. for 19 h under nitrogen protection, allowed to stand at 4° C. for 5.5 h, centrifuged at 5000 rpm for 30 min, the precipitate was washed with anhydrous ethanol and deionized water, and dried under vacuum at 50° C. to constant weight to obtain modified silica.
[0079] This embodiment also provides a method for preparing the automotive insulating coating, comprising the following steps: adding modified acrylic resin to deionized water, stirring at 500 rpm for 30 min, adding modified silica, dispersant, defoamer, and leveling agent, ultrasonicating at 25 kHz for 1 h, and stirring at a stirring speed of 1000 r / min for 14 min to obtain the automotive insulating coating.
[0080] This embodiment also provides the application of the automotive insulating coating in new energy vehicle batteries.
[0081] The only difference between Comparative Example 1 and Example 1 is that modified alumina is replaced by alumina.
[0082] The only difference between Comparative Example 2 and Example 1 is that silicon dioxide is used instead of modified silicon dioxide.
[0083] Experimental Example 1: The insulating coating prepared in Examples 1-3 was applied to the outer shell of a workpiece of a new energy vehicle battery by air spraying. The coating film thickness was 80 μm and the coating was heated and cured at 60°C for 8 h. The adhesion and hardness of the coating were tested. The adhesion test was carried out in accordance with the method specified in GB / T9826-1998. 100 / 100 means that 10×10 grids were scratched on the coating. After the test, no coating fell off in any of the 100 grids. The hardness test was carried out on a QHQ pencil scratch hardness tester in accordance with GB / T6739-2006.
[0084] Table 1:
[0085]
[0086] The results in Table 1 show that the insulating coatings prepared in Examples 1-3 have an adhesion of 100 / 100 and a hardness of 3H, which is acceptable, indicating that the insulating coating for automobiles of the present invention has good adhesion and hardness and excellent performance.
[0087] Experimental Example 2: The surface insulation resistance coefficient of the coating was tested according to the method of GB / T2522-2017. The coatings of Examples 1-3 and Comparative Examples 1-2 were heat cured at 60°C for 8 h, and the insulation resistance coefficient was tested using an insulation resistance tester. The results are as follows: Figure 1 shown.
[0088] Figure 1 The results show that the insulation resistance coefficient of Examples 1-3 is higher than that of Comparative Examples 1-2. Comparative Example 1 uses aluminum oxide to replace modified aluminum oxide, and aluminum oxide is not cross-linked and grafted into the acrylic resin, and the dispersibility decreases. Comparative Example 2 uses silicon dioxide to replace modified silicon dioxide, and the dispersibility is poor, and the insulation decreases. The results show that the insulation coating for automobiles of the present invention has good insulation performance.
[0089] Experimental Example 3: The water resistance of the paint coating was tested according to the GB / T1733-1993 method. The results are shown in Table 2.
[0090] Table 2:
[0091]
[0092] The results in Table 2 show that the water resistance of Example 1-3 is better than that of Comparative Example 1-2. Replacing modified alumina with alumina and replacing modified silica with silica will reduce the interface bonding performance of the material, weaken the degree of crosslinking, reduce hydrophobicity, and reduce water resistance. The results show that the automotive insulation coating of the present invention has good water resistance.
[0093] Experimental Example 4: The wear resistance of the insulating coatings of Examples 1-3 and Comparative Examples 1-2 was tested by using an RCA paper bag wear tester with a load of 175 g. The number of times the coating was worn was recorded. The samples and abrasive media were placed in an environment of 23±2°C and 50±10% relative humidity for 24 h before testing. The results are as follows: Figure 2 shown.
[0094] Figure 2 The results show that the wear resistance of Examples 1-3 is better than that of Comparative Examples 1-2, indicating that the modified alumina and modified silica of the automotive insulating coating of the present invention have good dispersibility and can effectively improve the wear resistance of the coating.
[0095] Experimental Example 5: The impact resistance of the coatings in Examples 1-3 and Comparative Examples 1-2 was tested according to GB / T1732-93 "Determination of impact resistance of paint films". The results are as follows: Figure 3 shown.
[0096] Figure 3 The results show that the coatings prepared in Examples 1-3 have better impact resistance than those prepared in Comparative Examples 1-2, indicating that the automotive insulating coating of the present invention has high mechanical strength and good impact resistance.
[0097] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. An insulating coating for automobiles, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of modified acrylic resin, 15-18 parts of modified silicon dioxide, 2-3 parts of dispersant, 0.5-0.7 parts of defoamer, 0.3-0.5 parts of leveling agent and 80-100 parts of deionized water; The preparation method of the modified acrylic resin comprises the following steps: (1) adding aluminum trichloride to deionized water, stirring, adding ethylenediamine dropwise, heat treating at 180-200° C., cooling, centrifuging, washing the precipitate, and drying to obtain aluminum hydroxide; (2) adding the aluminum hydroxide obtained in step (1) to deionized water, ultrasonically treating the mixture to obtain a mixed solution A, adding triethoxy-2-propylenesilane to tetrahydrofuran, ultrasonically treating the mixture to obtain a mixed solution B, adding the mixed solution B to the mixed solution A, stirring, standing, centrifuging, washing the precipitate, and drying to obtain modified aluminum oxide; (3) adding the modified alumina obtained in step (2) to n-butanol, heating after ultrasonication, introducing nitrogen, adding styrene, acrylic acid, butyl acrylate, methyl methacrylate and dibenzoyl peroxide, reacting, and removing n-butanol under reduced pressure to obtain a modified acrylic resin; The preparation method of the modified silicon dioxide comprises the following steps: (a) adding silica to tetrahydrofuran, ultrasonicating, and obtaining a silica dispersion; dissolving APTES in tetrahydrofuran to obtain an APTES solution, adding the APTES solution to the silica dispersion, heating to reflux, cooling, centrifuging, and drying to obtain aminosilica; (b) adding malonic acid to deionized water to obtain a malonic acid solution, dissolving CDI in tetrahydrofuran to obtain a CDI solution, adding the CDI solution dropwise to the malonic acid solution under nitrogen protection, stirring after the addition is complete, then adding the aminosilica obtained in step (a), continuing to stir, centrifuging, washing the precipitate, and drying to obtain carboxyl silica; (c) adding the carboxysilica obtained in step (b) to tetrahydrofuran, and subjecting to ultrasonic treatment to obtain a carboxysilica dispersion, and adding 1-hydroxybenzotriazole and N-N'-dicyclohexylcarbodiimide to the carboxysilica dispersion, and stirring to obtain an activated carboxysilica dispersion; (d) dissolving curcumin in tetrahydrofuran to obtain a curcumin solution, mixing the activated carboxyl silica dispersion obtained in step (c) with the curcumin solution, reacting under nitrogen protection, standing, centrifuging, washing the precipitate, and vacuum drying to obtain modified silica.
2. The automotive insulating coating according to claim 1, characterized in that: In step (1), the ratio of aluminum chloride to deionized water is 1 g:20 mL; the ratio of aluminum chloride to ethylenediamine is 15 g:8 mL.
3. The automotive insulating coating according to claim 2, characterized in that: In step (2), in the mixed solution A, the ratio of aluminum oxide to deionized water is 2 mg:1 mL; in the mixed solution B, the ratio of triethoxy-2-propylenesilane to tetrahydrofuran is 2-3 mg:1 mL; and the volume ratio of the mixed solution A to the mixed solution B is 1:
1.
4. The automotive insulating coating according to claim 3, characterized in that: In step (3), the ratio of the modified alumina to n-butanol is 1 g:100 mL; the mass ratio of the modified alumina, styrene, methyl methacrylate, acrylic acid, butyl acrylate and dibenzoyl peroxide is 2:16-18:32:6-7:45:0.8-1.
2.
5. The automotive insulating coating according to claim 4, characterized in that: In step (a), the amount ratio of silicon dioxide to tetrahydrofuran in the silicon dioxide dispersion is 1 g:12-15 mL; the amount ratio of APTES to tetrahydrofuran in the APTES solution is 1 g:1.5-2 mL; and the mass ratio of APTES to silicon dioxide is 2-3:
1.
6. The automotive insulating coating according to claim 5, characterized in that: In step (b), the dosage ratio of malonic acid to deionized water in the malonic acid solution is 1 g: 4-6 mL; the dosage ratio of CDI to tetrahydrofuran in the CDI solution is 1 g: 5-7 mL; the mass ratio of malonic acid to CDI is 1: 0.6-0.8; and the mass ratio of aminosilica to malonic acid is 1: 2-3.
7. The automotive insulating coating according to claim 6, characterized in that: In step (c), the amount ratio of carboxysilica to tetrahydrofuran in the carboxysilica dispersion is 1 g:15 mL; the mass ratio of carboxysilica, 1-hydroxybenzotriazole and N,N'-dicyclohexylcarbodiimide is 5:1:
2.
8. The automotive insulating coating according to claim 7, characterized in that: In step (d), the amount ratio of curcumin to tetrahydrofuran in the curcumin solution is 1 g: 8-10 mL; the volume ratio of the curcumin solution to the activated carboxyl silica dispersion is 1: 1.8-2.
2.
9. A method for preparing the automotive insulating coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: Add the modified acrylic resin into deionized water, stir, add modified silicon dioxide, dispersant, defoamer, leveling agent, ultrasonicate, stir for 12-15 minutes, and obtain the insulating coating for automobile.
10. An application of the automotive insulating coating according to any one of claims 1 to 8, characterized in that: Application of the automotive insulating coating in new energy vehicle batteries.
Citation Information
Patent Citations
Zero VOC two-component fire-retardant expansion coating for new energy battery shell and preparation method thereof and battery compartment
CN116333566B
Length-to-diameter-ratio-controllable AlOOH nano-adjuvant and preparation method thereof
CN109432417A
Water-based single-component wood coating and preparation method thereof
CN111171691A